Nelson textbook of pediatrics - Kliegman, Robert; Nelson, Waldo E. (Waldo Emerson), 1898-1997. (Philadelphia, PA : Elsevier/Saunders, 2011)
Nelson Textbook of Pediatrics has been the world's most trusted pediatrics resource for nearly 75 years. Drs. Robert Kliegman, Bonita Stanton, Richard Behrman, and two new editors-Drs. Joseph St. Geme and Nina Schor-continue to provide the most authoritative coverage of the best approaches to care. This streamlined new edition covers the latest on genetics, neurology, infectious disease, melamine poisoning, sexual identity and adolescent homosexuality, psychosis associated with epilepsy, and more. Best of all, the expanded online access at www.expertconsult.com features the full text, case studies, new references and journal articles, Clinics articles, and exclusive web-only content so that you get even more out of this invaluable reference. - Publisher.
Pt. I: The field of pediatrics -- Pt. II: Growth, development and behavior -- Pt. III: Behavioral and psychiatric disorders -- Pt. IV: Learning disorders -- Pt. V: Children with special needs -- Pt. VI: Nutrition -- Pt. VII: Pathophysiology of body fluids and fluid therapy -- Pt. VIII: Pediatric drug therapy -- Pt. IX: The acutely ill child -- Pt. X: Human genetics -- Pt. XI: Genetic disorders of metabolism -- Pt. XII: The fetus and the neonatal infant -- Pt. XIII: Adolescent medicine -- Pt. XIV: Immunology -- Pt. XV: Allergic disorders -- Pt. XVI: Rheumatic diseases of childhood -- Pt. XVII: Infectious diseases -- Pt. XVIII: The digestive system -- Pt. XIX: Respiratory system -- Pt. XX: The cardiovascular system -- Pt. XXI: Diseases of the blood -- Pt. XXII: Cancer and benign tumors -- Pt. XXIII: Nephrology -- Pt. XXIV: Urologic disorders in infants and children -- Pt. XXV: Gynecologic problems of childhood -- Pt. XXVI: The endocrine system -- Pt. XXVII: The nervous system -- Pt. XXVIII: Neuromuscular disorders -- Pt. XXIX: Disorders of the eye -- Pt. XXX: The ear -- Pt. XXXI: The skin -- Pt. XXXII: Bone and joint disorders -- Pt. XXXIII: Environmental health hazards -- Pt. XXXIV: Laboratory medicine.
Voume 1 & 2.
Includes bibliographical references and index.
Keywords: Pediatrics; Pediatrics